Experimental Investigation Of Relative Performance Of Water Based Tio2 And Zno Nanofluids In A Double Pipe Heat Exchanger - Ramaraju, Ramgopal Varma; Reddy, M. Chandra Sekhara; Rao, Veeredhi Vasudeva (2013)
This paper deals with experimental determination of convective heat transfer coefficient in a counter flow double pipe heat exchanger using water based TiO2, ZnO nanofluids with 0.002% & 0.004% volume concentrations. Experiments are conducted at various Reynolds numbers ranging from 1600 to 6100. From the experimental results it is found that heat transfer coefficient increases with increase of volume concentration of nanoparticles as well as Reynolds number. Enhancement of heat transfer coefficient between nanofluids with 0.002% volume concentration of TiO2, ZnO and the inner walls of copper tube in a double pipe heat exchanger increased up to 30.37% and 57.31% respectively. The enhancements are as high as 66.12% and 78.30% when the volume concentration is 0.004% of TiO2 and ZnO respectively for same set of operating conditions when compared to pure water at Reynolds number 6100. The experimental results are presented in graphical form. The variation of heat transfer coefficient in both dimensional and non-dimensional form are presented as a function of Reynolds number for different volume concentrations of nanofluids. The effectiveness of heat exchanger is also presented as a function of volume concentration of nanofluids.